Dampak Riba dalam Kehidupan Ekonomi: Perspektif Syariah dan Ekonomi Kontemporer - Aida Efendi; Carina Septiani; Saidah Syakira; Taura Zilhazem; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Usury is one of the concepts that is forbidden in Islamic law and has a significant impact on the economy of individuals and society (Arafah et al., 2019). The background of this study focuses on the importance of a deep understanding of usury to build awareness of its economic implications. The purpose of this study is to identify and explain the types of usury, as well as to understand the legal basis that prohibits the practice in the Qur'an and Hadith. The research method used is a qualitative method based on literature review, by analyzing primary and secondary sources related to Islamic law and sharia economics. The results of the study indicate that usury consists of several categories that have different implications, and the application of the law on usury can encourage the development of a fairer financial system. The discussion includes an analysis of the social and economic impacts of usury practices, as well as alternative sharia financial products that can be applied to replace usury. This study is expected to contribute to public understanding of usury and encourage the implementation of sharia principles in the modern economy.